2010
DOI: 10.1590/s1516-35982010001100008
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de populações de Lotus corniculatus L. com maior tolerância ao alumínio em solução nutritiva

Abstract: RESUMO -O experimento foi realizado com o objetivo de selecionar genótipos de Lotus corniculatus L. (Draco, SãoGabriel e UFRGS) mais tolerantes ao alumínio, utilizando-se a técnica de seleção em solução nutritiva. A solução continha 200 μmol/L de cálcio (CaCl 2 ), 100 μmol/L de alumínio (AlCl 3 ) e pH controlado na faixa de 4,1 a 4,3. Realizaram-se dois ciclos de seleção, nos quais as plântulas foram selecionadas pelo comprimento final das radículas. Posteriormente, avaliou-se o ganho genético alcançado nos ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The opposite was noted for UFRGS, which showed quadruple amount of polyphenols in soil with Al compared to that when it was cultivated in soil without Al (Table 1). Since previous studies have shown that this genotype has more Al tolerance than other genotypes of common birdsfoot trefoil (Draco and São Gabriel) (SANTOS et al, 2007(SANTOS et al, , 2008JANKE et al, 2010), the findings of this study indicate a possible association between tolerance to acidity and production of PCs in this species. If such a relationship is confirmed, the catechin and epicatechin contents could be used as chemical markers for Al tolerance.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The opposite was noted for UFRGS, which showed quadruple amount of polyphenols in soil with Al compared to that when it was cultivated in soil without Al (Table 1). Since previous studies have shown that this genotype has more Al tolerance than other genotypes of common birdsfoot trefoil (Draco and São Gabriel) (SANTOS et al, 2007(SANTOS et al, , 2008JANKE et al, 2010), the findings of this study indicate a possible association between tolerance to acidity and production of PCs in this species. If such a relationship is confirmed, the catechin and epicatechin contents could be used as chemical markers for Al tolerance.…”
Section: Resultssupporting
confidence: 55%
“…Thus, the fact that only UFRGS maintained the epicatechin:catechin proportion in both soil acidity conditions might be related to the selection process to which it was submitted. This genotype is preferred as forage material owing to its higher tolerance to Al (SANTOS et al, 2007;JANKE et al, 2010). Among the possible causes of Al tolerance is the amount of polyphenols, such as catechins that can detoxify this element by chelation (CHEN et al, 2009).…”
Section: Speciesmentioning
confidence: 99%